Alkebulan Symphony: Arts, Crafts and Culture in Architecture - ALAWODE, Musa Ajibola; SULEMAN, Taofeek Adedotun (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This paper examines the interconnection between the art, craft, culture and architecture of Africa. In doing this, it gives a brief explanation of African art, craft, architecture and culture. It also examines the manifestation of culture in African architecture and the role of art in architecture. The study adopts qualitative research design, using historical and descriptive approaches. It equally relies on secondary sources of data collection. In the course of research, it was discovered that art, craft, culture and architecture are inseparable, because they complement one another. Also, culture manifests in various ways in the architecture of Africa through kinship, religion, ornamentation, among others. It was further observed that art has inspired many architectural pieces in Africa. The study concludes by suggesting various ways of applying African craftsmanship in architecture to create a postcolonial identity.